Comparison of Ocular Trauma Score and Penetrating Ocular Trauma Score in Predicting Visual Outcome in Children - Munir , Faraz; Jehangir, Ramsha; Parvez, Ayesha; Farooq, Amna; Khokhar, Hira Shuja; Shahzad, Taiba (Indus Journal of Bioscience Research, 2024)
Background: Previously, no standardized system existed for naming and managing ocular trauma. The Ocular Trauma Score (OTS) was introduced to predict visual outcomes in patients with ocular injuries, proving valid in adults. However, its effectiveness in children was uncertain. To address this, the Penetrating Ocular Trauma Score (POTS) was developed specifically for pediatric cases. Despite these advancements, no consensus emerged nationally or internationally on whether OTS or POTS was the superior predictor of visual outcomes in children with ocular injuries. Objective: This study aimed to determine the more reliable scoring system for predicting visual outcomes in children after ocular trauma. A total of 34 patients aged 1 to 12 years with penetrating ocular injuries were included. Consent was obtained from the parents or guardians, and the study’s procedure was fully explained. A comprehensive eye examination, covering variables for both OTS and POTS, was conducted at the time of injury, and patients were followed for six months. Results were compared using cross-tabulation with the original OTS and POTS. Results: Of the 34 patients, 23 (67.6%) were male and 11 (32.4%) females, with a mean age of 6.7 years (range 1–15 years). Right-eye injuries occurred in 21 (61.8%) patients, and left-eye injuries in 13 (38.2%). Injuries most frequently occurred at home (61.8%) and in the street (26.5%), with stones (20.6%) and knives (17.6%) as common injury objects. An unclean wound was present in 22 (64.7%) cases, and traumatic cataract developed in 17 (50%) patients. Initial visual acuity (VA) ranged from PL to 20/20 (PL in 47%), while final VA ranged from NPL to 20/20 (PL in 26.5%). OTS results showed variable accuracy in groups 1–3 but matched predictions in groups 4 and 5. For POTS, groups 1, 2, 3, and 5 aligned with expected outcomes. Conclusion: POTS demonstrated higher reliability than OTS in predicting visual outcomes in pediatric ocular trauma cases